2015
DOI: 10.4067/s0717-92002015000300014
|View full text |Cite
|
Sign up to set email alerts
|

La frugivoría por cánidos nativos (Lycalopex spp.) y alóctonos (Canis lupus familiaris) reduce la germinación de semillas de litre (Lithrea caustica) en Chile central

Abstract: La frugivoría por cánidos nativos (Lycalopex spp.) y alóctonos (Canis lupus familiaris) reduce la germinación de semillas de litre (Lithrea caustica) en Chile central Frugivory by native (Lycalopex spp.) and allochthonous (Canis lupus familiaris) canids reduces the seed germination of litre (Lithrea caustica) in central Chile

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
4
0
3
Order By: Relevance
“…Seed as L. caustica and R. ephedra are heavier than the others and its dispersal mechanism are barochory-endozoochory and barochory respectively. Whereas Lycalopex culpaeus and O. cuniculus have been described as dispersers for L. caustica (Medan & Aagesen 1995;Catro et al, 2008;Morales-Paredes et al, 2015), M. boaria seeds are dispersed by Colorhamphus parvirostris, by Xolmis pyrope and by Anairetes parulus (Reid & Armesto, 2011). The lightest seed of this study is a winged seed of Q. saponaria and its dispersal mechanism is meteoranemochory (Table 1).…”
Section: Seed Species Featuresmentioning
confidence: 65%
See 1 more Smart Citation
“…Seed as L. caustica and R. ephedra are heavier than the others and its dispersal mechanism are barochory-endozoochory and barochory respectively. Whereas Lycalopex culpaeus and O. cuniculus have been described as dispersers for L. caustica (Medan & Aagesen 1995;Catro et al, 2008;Morales-Paredes et al, 2015), M. boaria seeds are dispersed by Colorhamphus parvirostris, by Xolmis pyrope and by Anairetes parulus (Reid & Armesto, 2011). The lightest seed of this study is a winged seed of Q. saponaria and its dispersal mechanism is meteoranemochory (Table 1).…”
Section: Seed Species Featuresmentioning
confidence: 65%
“…Seed weight, length and width were calculated with the mean of N = 100 seeds. Reported fruiting period and dispersal mechanism obtained from 1Morales-Paredes et al, (2015),2 Reid & Armesto (2011),3 Montenegro et al (1989),4 Velazco et al, 2018, 5 Medan & Arce (1999…”
mentioning
confidence: 99%
“…One recent study evaluated the effect of carnivores on seed dispersal and germination, and reported that seed consumption by these animals might increase the probability of germination after passing through its digestive tract (Morales‐Paredes, Valdivia, & Sade, ). Our observations of the single rodent visitor and several studies (Heithaus, ; Janzen, ) indicate this may not be the case in our study system.…”
Section: Discussionmentioning
confidence: 99%
“…Todas las semillas fueron colocadas en una germinadora a una temperatura constante de 25°C, fotoperíodo de 12 horas y humedad relativa del 50%. Se consideró la germinación de la semilla a partir de la aparición de la radícula (Fernández y Johnston, 1986) Al final de cada prueba de germinación se realizó un segundo análisis de viabilidad (Morales-Paredes et al, 2015), para esto se tomaron las semillas no germinadas después de los 42 días de haber registrado la primera germinación y se determinó si el embrión estaba vivo o no, aplicando la misma prueba de tetrazolio descrita anteriormente.…”
Section: Viabilidad Y Germinación De Las Semillasunclassified
“…Sin embargo, esto no puede tomarse como un patron general, en Chile las semillas de Lithrea caustica alcanzaron el 24 % de germinación después de haber pasado por el tracto digestivo de Perros domésticos (Canis lpus familiaris) y de los zorros, Lycalopex culpeus y L. griseus, en contra del 45% de germinación en las semillas colectadas para el control (Morales-Paredes et al, 2015), de ahí que es necesario evaluar cada caso de manera individual.…”
Section: Introductionunclassified